Measuring Mathematical Literacy Skills of Indonesian Junior High School Students in Solving PISA-Like Problems - Simbolon, Asep; Nurjanah, Nurjanah (FKIP Universitas Lampung, 2024)
Measuring Mathematical Literacy Skills of Indonesian Junior High School Students in Solving PISA-Like Problems. Objective: In the current digital era, students’ mathematical literacy skills are important for every student. This study aims to measure junior high school students’ mathematical literacy skills in solving PISA-like problems and to analyze the primary elements contributing to students' challenges in solving mathematical literacy PISA-like problems oriented to the PISA framework. Methods: This research uses a qualitative method with a case study design. The subjects are 25 grade-ninth students selected by purposive sampling. Data collection used mathematical literacy tests, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion. Data triangulation was also used to verify data validity by comparing test results and interviews to confirm the validity of the data obtained. Findings: The primary elements contributing to students' challenges in addressing PISA-like-oriented mathematical literacy difficulties are a lack of familiarity with mathematical literacy questions, and classroom instruction not focused on contextual learning. These issues indicate that students lack exposure to real-world applications of mathematical concepts, which are crucial in developing problem-solving skills. Additionally, the absence of contextual learning means that students are not provided with opportunities to apply their mathematical knowledge to solve practical, everyday problems. Conclusion: Students’ competency in addressing PISA-like problems related to four contents was low. According to the indicators of mathematical literacy, sixty percent of students could effectively formulate the contextual situation of the problem concerning the quantity of material at levels 1 and 2. Meanwhile, other indicators “employed and interpreted” on shape and space content, data and uncertainty, and change and relationship at levels 3 up to 6 are still in the low category. Keywords: mathematical literacy, PISA-like problems, PISA framework, junior high school.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1259-1272